PERWATAKAN TOKOH UTAMA DALAM NOVEL DIAN YANG TAK KUNJUNG PADAM KARYA SUTAN TAKDIR ALISJAHBANA - Hardi, Novri; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research background is motivated by the desire to find a character from the novel title Dian yang Tak Berkunjung Padam by Sutan Takdir Alisjahbana. The general problem in this research is